(untitled) (Biological Sciences - PJSIR, 2008)
New peroxo complexes of Th(IV) have been synthesized and characterized by elemental analyses and various physicochemical techniques. The complexes were found to oxidize allyl alcohol and triphenylphosphine as well as triphenylarsine to their respective oxides. The molar conductance values and six fold coordination indicate that all the complexes are 1:1 electrolytes in dimethylsulphoxide revealing their ionic characters. The complexes display v(C=O) bands at 1625 cm-1 and v(C-O) bands at 1405 cm-1, significantly lower than the values of amino acid ( 1630 cm-1 and 1412 cm-1) indicating the coordination of amino acids through their carboxylate anion. The Th(IV) complexes display v(M=O) modes in the region 910-999 cm-1. The broad band observed at about 3244-3386 cm-1 for v(N-H) modes indicates the coordination of amino group through nitrogen atom of amino acid. These are predominantly O-O stretching v1, the symmetric M-O stretch v2 and the antisymmetric M-O stretch v3. The characteristic v1(O-O) modes of the complexes appear at 800-840 cm-1. It is observed that the v1 mode decreases with the increase of atomic number of the metal in a particular group. The magnetic moment values of dioxothorium (IV) complexes revealed them to be diamagnetic in nature, suggesting there were no changes in the oxidation states of the metal ions upon complexation. The electronic spectral data of the complexes showed bands at 260-350 nm region due to the charge transfer band only.